The Setback in Political Entrepreneurship and Employment Dualization in Japan, 1998–2012. (18th May 2015) - Yun, Ji‐Whan
Abstract: Scholars are mainly concerned about how policy makers in advanced countries have succeeded in dualizing labour market regulations in a way to realize their vision or to represent powerful industrial interests. However, Japan's recent experiences suggest the possibility that this dualization is not such a straightforward outcome. This study argues that as Japan's political entrepreneurs have undergone setbacks in their reform attempt to overcome the tradition of employment dualism, they have improvised to close the reform process by institutionalizing this tradition. This study corroborates the argument by investigating state‐industry conflicts over the revisions of the Worker Dispatch Law in 1999, 2003 and 2012.